2008
DOI: 10.1287/orsc.1070.0294
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Impact of Employee Turnover on Performance: The Role of Process Conformance

Abstract: W e examine the impact of employee turnover on operating performance in settings that require high levels of knowledge exploitation. Using 48 months of turnover data from U.S. stores of a major retail chain, we find that, on average, employee turnover is associated with decreased performance, as measured by profit margin and customer service. The effect of turnover on performance, however, is mitigated by the nature of management at the store level. The particular aspect of management on which we focus is proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
223
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(249 citation statements)
references
References 26 publications
15
223
1
6
Order By: Relevance
“…Specifically, we study 15 UK listed football clubs in order to assess the effect on shareholder wealth of the 1 See, for example, the arguments and papers cited by Davidson, Worrell and Fox (1996), Panayotopoulou, Bourantas & Papalexandris (2003), and Pfeffer (1996). Most empirical research has concentrated on the effect of human resource aspects that can be easily measured, such as formal education, training, labor quality, managerial skills, satisfaction, eg., see Edmans (2007), Griliches and Regev (1995), Hitt, Bierman, Shimizu & Kochhar (2001), Lynch and Black (1995) and Ton and Huckman (2008). Research on the effects of human capital on equity value has been very limited (see Abdel-khalik, 2003, inter alia). purchase, sale and lending of players.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we study 15 UK listed football clubs in order to assess the effect on shareholder wealth of the 1 See, for example, the arguments and papers cited by Davidson, Worrell and Fox (1996), Panayotopoulou, Bourantas & Papalexandris (2003), and Pfeffer (1996). Most empirical research has concentrated on the effect of human resource aspects that can be easily measured, such as formal education, training, labor quality, managerial skills, satisfaction, eg., see Edmans (2007), Griliches and Regev (1995), Hitt, Bierman, Shimizu & Kochhar (2001), Lynch and Black (1995) and Ton and Huckman (2008). Research on the effects of human capital on equity value has been very limited (see Abdel-khalik, 2003, inter alia). purchase, sale and lending of players.…”
Section: Introductionmentioning
confidence: 99%
“…Many empirical studies support this view. For example, Ton and Huckman found that collective turnover will bring about a decline in organizational profit margins [11]. Shaw et al found that the turnover rate of each unit will lead to a decline in sales of about $1500 per unit [12].…”
Section: The Results Of Collective Turnovermentioning
confidence: 99%
“…Indeed, overall profits fall following employee departure (Ton & Huckman, 2008). As such, understanding the causes of turnover and retaining employees are highly relevant to organizational health.…”
Section: Organizational Nostalgia Reduces Turnover Intentions Via Incmentioning
confidence: 99%
“…Here, we focus on a particularly costly outcome, namely, turnover. Turnover is costly, because investments in human resources, such as training or expertise, are lost to the organization when employees decide to leave (Ton & Huckman, 2008;Van Dick et al, 2004).…”
Section: Organizational Nostalgia Reduces Turnover Intentions Via Incmentioning
confidence: 99%
See 1 more Smart Citation